KONSEP EKONOMI ISLAM VERSI ABDULLAH SAEED - Asriyana, Asriyana; Masse, Rahman Ambo; Kara, Muslimin (Jurnal PenKoMi : Kajian Pendidikan dan Ekonomi, 2024)
This article discusses the understanding of economic concepts in Islam, which has become the subject of extensive debate and has attracted interest from various backgrounds. One of the views that has emerged is the version put forward by Abdullah Saeed. In his version, Saeed discusses the basic principles of Islamic economics, which include the principles of justice, equal distribution, shared ownership, and the prohibition of usury. Emphasis on community empowerment through economic practices in accordance with Islamic teachings. This research is a qualitative descriptive study. The aim of this research is to interpret and explain data relating to the current situation, attitudes and views that occur in society, the conflict between two or more situations, the influence of a condition, or other things. This article will explore the key points in Abdullah Saeed's version of the concept of Islamic economics, as well as its impact on contemporary economic thought and economic practice in the Muslim world.